A Review on Maximum Productivity of Land Use in Urban Project Development - Herlambang Sucahyo; Yani Rahmawati; Christiono Utomo (Institut Teknologi Sepuluh Nopember, 2017)
The Regional Budget Fiscal Year of Surabaya in 2017 is IDR 8,561,848,147,400, where Regional Revenue (PAD) is projected as much as IDR 4,212,569,176,921 along with Regional Wealth Management IDR 166,311,576,799. That revenue is derived from the activity of managing land asset. The total assets of Surabaya is currently 60,115,651.23 m2, where 84% of the area already has its land use, and 937,911.35 m2 or 0,56% is used for commercial use. Some of the assets are not optimally used for PAD yet. The city loses its opportunity in gaining maximal revenue because the assets are not developed properly, where the assets are mostly located in the main corridor of the city or primary artery. Highest and Best Use (HBU) analysis is found to be one of important technique in finding best alternative to be used in developing vacant land and existed improved property. This study analyzes the HBU practices in developing the government assets of Surabaya, especially the area that is placed near the riverside. Literature review and in depth interview to stakeholders are used to obtain data. The data is then analyzed by using descriptive analysis. Based on analysis, it is found that mixed use commercial building come out as best alternative in developing the assets.